Video training and certification program improves reliability of postischemic neurologic deficit measurement in the rat. Issue 12 (December 2016) - Taninishi, Hideki; Pearlstein, Molly; Sheng, Huaxin; Izutsu, Miwa; Chaparro, Rafael E; Goldstein, Larry B; Warner, David S
Scoring systems are used to measure behavioral deficits in stroke research. Video-assisted training is used to standardize stroke-related neurologic deficit scoring in humans. We hypothesized that a video-assisted training and certification program can improve inter-rater reliability in assessing neurologic function after middle cerebral artery occlusion in rats. Three expert raters scored neurologic deficits in post-middle cerebral artery occlusion rats using three published systems having different complexity levels (3, 18, or 48 points). The system having the highest point estimate for the correlation between neurologic score and infarct size was selected to create a video-assisted training and certification program. Eight trainee raters completed the video-assisted training and certification program. Inter-rater agreement (κ score) and agreement with expert consensus scores were measured before and after video-assisted training and certification program completion. The 48-point system correlated best with infarct size. Video-assisted training and certification improved agreement with expert consensus scores (pretraining = 65 ± 10, posttraining = 87 ± 14, 112 possible scores, P < 0.0001), median number of trainee raters with scores within ±2 points of the expert consensus score (pretraining = 4, posttraining = 6.5, P < 0.01), categories withκ > 0.4 (pretraining = 4, posttraining = 9), and number of categories with an improvement in theκ score from pretraining to posttraining (n = 6). Video-assisted training and certification improved trainee inter-rater reliability and agreement with expert consensus behavioral scores in rats after middle cerebral artery occlusion. Video-assisted training and certification may be useful in multilaboratory preclinical studies.